KAJIAN POTENSI HIDROLOGI EMBUNG IRIGASI WAE ROBANG DI KABUPATEN ROTE NDAO - Nurasiyah, Siti (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2015)
KAJIAN POTENSI HIDROLOGI EMBUNG IRIGASI WAE ROBANG DI KABUPATEN ROTE NDAOStudy The Potential Of Hidrology Wae Robang Irrigation Retention Basin In Rote Ndao DisrtrictSiti NurasiyahDepartemen Pendidikan Teknik Sipil, Universitas Pendidikan Indonesiaemail: iisnurasiyah82@yahoo.comAbstractRote Ndao District is one of the districts in the province of NTT, which has a fairly extensive irrigation areas and potential but less discharge to irrigate the irrigation area. Rote Ndao District has topography is hilly and much of the basin area can hold water, so one way to solve this problem is to build retention basin to hold excess water during the rainy season. Wae Robang retention basin is one of the retention basin will be built in Rote Ndao District. One aspect that must be examined in the planning of retention basin is hydrological analysis. The purpose of the analysis of hydrology at the location of Robang Wae retention basin is to assess the potential of existing hydrological includes inflows fill retention basin, retention basin reservoirs, and flood discharge plan. From the results of the hydrological analysis showed that the volume of water that can fill an Wae Robang retention basin during the rainy season amounted to 1,774,029 m3, retention basin reservoir design capacity Wae Robang retention basin amounted to 1,348,859 m3, and the flood discharge plan with a return period of 50 years for the spillway Wae Robang retention basin amounted to 21.71 m3/ sec.Keywords: Wae Robang, retention basin, hydrologi AbstrakKabupaten Rote Ndao merupakan salah satu kabupaten di provinsi NTT yang memiliki areal irigasi yang cukup luas dan cukup potensial tetapi kekurangan debit air untuk mengairi areal irigasi tersebut. Kabupaten Rote Ndao ini memiliki kondisi topografi yang berbukit-bukit dan banyak daerah cekungan yang dapat menampung air, maka salah satu cara untuk menanggulangi masalah ini adalah dengan membangun embung yang berguna untuk menampung air yang berlebihan pada waktu musim hujan. Embung Wae Robang merupakan salah satu embung yang akan dibangun di Kabupaten Rote Ndao. Salah satu aspek yang harus ditelaah dalam perencanaan embung adalah analisis hidrologi. Tujuan dari analisis hidrologi di lokasi embung Wae Robang ini adalah untuk mengkaji potensi hidrologi yang ada meliputi aliran masuk yang mengisi embung, tampungan embung, dan debit banjir rencana. Dari hasil analisis hidrologi didapatkan bahwa volume air yang dapat mengisi kolam Embung Wae Robang selama musim hujan adalah sebesar 1.774.029 m3, kapasitas tampung desain embung Wae Robang adalah sebesar 1.348.859 m3, dan debit banjir rencana dengan kala ulang 50 tahun untuk pelimpah embung Wae Robang adalah sebesar 21,71 m3/det.Kata kunci : Wae Robang, embung, hidrologi